Transcriptome profiling reveals a global response in harmful dinoflagellate Karlodinium veneficum to naturally-occurring bacterial algicides - Wang, Yanfei; Coyne, Kathryn J. (Frontiers in Marine Science, 2023)
Dinoflagellates are among the most toxigenic phytoplankton that cause harmful algal blooms; they can produce toxins that accumulate through the aquatic food chains to cause illness and even death in marine animals and humans. Shewanella sp. IRI-160 is a naturally-occurring bacterium that secretes a suite of algicidal compounds (collectively designated as IRI-160AA) specifically targeting dinoflagellates. Studies revealed IRI-160AA inhibited photosynthesis, while inducing cell cycle arrest, DNA damage, and reactive oxygen species (ROS) production, as well as other markers associated with programmed cell death (PCD). Recent research indicated that IRI-160AA contains ammonium and other compounds as active ingredients for its algicidal activity, while impacts by ammonium differed from the algicide with respect to photobiology. Here, transcriptomic analysis was conducted on the toxic dinoflagellate Karlodinium veneficum exposed to IRI-160AA to investigate the effects of this algicide at the molecular level. Transcriptomic analysis was also conducted on K. veneficum treated with ammonium to further differentiate its effects from IRI-160AA. Results demonstrated differential impacts by IRI-160AA and ammonium on K. veneficum at the molecular level and revealed a global response of K. veneficum to algicide exposure, supported by the enriched biological processes involved in regulating gene expression, protein activity, and morphology. Differentially expressed genes associated with stress and ROS response, DNA damage response, cell cycle checkpoint activation, and PCD were also identified in K. veneficum exposed to IRI-160AA. The potential involvement of a recovery mechanism from photodamage in K. veneficum induced by IRI-160AA was identified. Overall, results of this study further differentiated the impacts of ammonium from IRI-160AA on K. veneficum and illustrated the cellular mechanisms behind the algicidal effect. This research provided insights on algal response to bacterial derivatives in nature.